An Intuitive Calculus Book for Engineers Um Livro de Cálculo Intuitivo para Engenheiros - Gustavo Alexandre de Miranda (Universidade Estadual Paulista, 2010)
With the purpose of studying the history of calculus teaching and, particularly, the consequences of Calculus Made Easy (1910) in the mathematics education context, this work intends to make an historical analysis to clarify the connections between Silvanus Phillips Thompson (its author) and education in the early Twentieth Century, mainly mathematics education. Thompson was concerned about Physics and Radiology,however, at the dawn of the new century, his interests in technical education had also burgeoned. One of his goals was to demystify Calculus, tackling the subject intuitively - Calculus Made Easy. The book did not draw much respect from mathematicians and was acridly criticized. Keywords: Mathematics Education, History of Mathematics Education, Silvanus Phillips Thompson, Calculus Made Easy. Com o intuito de estudar a história do ensino de Cálculo e, mais especificamente, os desdobramentos do livro Calculus Made Easy (1910) no contexto da educação matemática, este trabalho procura fazer uma análise histórica que elucide as relações entre Silvanus Phillips Thompson (autor do livro) e a educação do início do século XX, particularmente a educação matemática. Thompson legou muito às áreas da física e da radiologia, porém, com a chegada do novo século, passou a se dedicar intensamente à educação técnica de seus compatriotas ingleses. Um de seus objetivos era desmistificar alguns conceitos do Cálculo, tratando o assunto de maneira intuitiva. Por esse motivo, o livro foi criticado por alguns matemáticos. Palavras-chave: Educação Matemática. História da Educação Matemática. Silvanus Phillips Thompson. Calculus Made Easy.